QUANTITATIVE ADJECTIVES IN KULISUSU LANGUAGE - Nurfarsil, Eca; Tambunan, Tambunan; Rohmana, Rohmana (Universitas Halu Oleo, 2020)
This research aimed at investigating the quantitative adjectives and semantic types of quantitative adjectives in Kulisusu language. The scope of this research was quantitative adjectives and semantic types of quantitative adjective meaning color, size, form and taste. The research questions of this study were